Percepção de mães beneficiárias ribeirinhas sobre o programa bolsa família: um olhar da psicologia econômica - SANTOS, Thamyris Maués dos (Universidade Federal do Pará, 2019)
The objective of the present dissertation is to investigate the economic characteristics of families benefiting from the program Bolsa Família (PBF) residents of an amazon riverside community and the perception of the mothers from these families about the program. For this reason it was made multiple case studies of four riverside families inhabitants of an island belonging to the city of Belém, capital of the state of Pará. Demographic and socioeconomic data were collected, besides retrospective and actual testimonials about the values related to the benefit of PBF and the future expectations of these families, as well as their consumption habits and their relation with the received resource. The main results point the importance of the PBF income in the family total budget. In general, the money obtained through the extraction of açaí is destined to supplement the expenses with alimentation and acquisition of furniture and home appliances and the money from the benefit is destined to goods that are enjoyed mainly by the children and their mothers like clothes, school expenses, and personal items. However, given the extreme diet vulnerability situation, the benefit was also spent with the purchase of food for the entire group and the acquisition of furniture and home appliances. The structural and socioeconomic characteristics are presented, among which are highlighted: the division of work, the savings, the use of credit cards, the existence of debts in commercial establishments, the importance of electric energy and the participation in the benefit of INCRA. In what concerns the perception of the mothers beneficiaries about the PBF, six themes were organized: the general perception about the PBF, the empowerment of the beneficiaries, the conditionalities of education and health and the changes in the perception of the husband‟s income, the frequency of expenses and in the supply of necessities. Altogether, the participants perceive the benefit as a positive aggregate in their family budget and fulfill the necessary conditionalities for their participation in the program. But, for a real break in the cycle of poverty, it is necessary the availability of quality public services, which create healthy and autonomous citizens.